2017
DOI: 10.4081/audiores.2017.168
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of the Clinical Characteristics and Post-Treatment Hearing Outcome in Idiopathic Sudden Sensorineural Hearing Loss

Abstract: The purpose of this retrospective study was to analyze the clinical characteristics and document hearing recovery in patients with idiopathic sudden sensorineural hearing loss (ISSNHL). 122 patients diagnosed with unilateral ISSNHL, from March 2009 to December 2014, were treated with oral steroids and pentoxifylline. Hearing change was evaluated by comparing pre-treatment and post-treatment pure-tone average (PTA) (500, 1K, and 2K Hz), and categorized into complete, partial, and no recovery of hearing. T-test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In most patients, tinnitus is associated with hearing loss [ 8 , 15 , 16 ]. The association between tinnitus and SSNHL is extremely high (66 to 93%) [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most patients, tinnitus is associated with hearing loss [ 8 , 15 , 16 ]. The association between tinnitus and SSNHL is extremely high (66 to 93%) [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study byPurushothaman Ganesan, Purushothaman Pavanjur, Out of 122 patients, 58% showed complete recovery, 28% had partial recovery, whereas 14% had no recovery. [12] We tried to correlate the maximum gain in hearing with the duration of onset of treatment. Duration of onset of treatment ranged from 1 day to 36 days with a mean of 10.8 days.…”
Section: Discussionmentioning
confidence: 99%
“…Different therapeutic approaches are based on the supposed pathophysiological mechanisms responsible for inner ear dysfunction. Therapies of idiopathic SSNHL include corticosteroids, vasodilators, anticoagulants, antioxidants, plasma expanders and HBOT [ 36 , 37 , 38 ]. The first-line treatment for idiopathic SSNHL are oral or/and intratympanic corticosteroids to reduce the supposed inflammatory response.…”
Section: Hbot In the Treatment Of Sudden Sensorineural Hearing Losmentioning
confidence: 99%